2016
DOI: 10.1089/ars.2015.6475
|View full text |Cite
|
Sign up to set email alerts
|

Salusin-β Promotes Vascular Smooth Muscle Cell Migration and Intimal Hyperplasia After Vascular InjuryviaROS/NFκB/MMP-9 Pathway

Abstract: Salusin-β promotes VSMC migration and vascular injury-induced intimal hyperplasia via MMP-9 accumulation due to NOX2 activation, followed by ROS production, IκBα phosphorylation and degradation, and p65-NFκB translocation. We propose that salusin-β may be important in the VSMC migration and neointima of some vascular diseases. Antioxid. Redox Signal. 24, 1045-1057.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
76
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(82 citation statements)
references
References 47 publications
6
76
0
Order By: Relevance
“…VSMCs in culture often mimic the synthetic phenotype, typically expressing MMP-2 in the presence of an autocrine or PDGF loop [37]. Some peptides, such as salusin-β, promote the migration of VSMCs through upregulation of MMP-2 and MMP-9 [18,38]. Here, we found that salusin-α treatment dramatically inhibited MMP-2 and MMP-9 expression in plaques (Fig.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…VSMCs in culture often mimic the synthetic phenotype, typically expressing MMP-2 in the presence of an autocrine or PDGF loop [37]. Some peptides, such as salusin-β, promote the migration of VSMCs through upregulation of MMP-2 and MMP-9 [18,38]. Here, we found that salusin-α treatment dramatically inhibited MMP-2 and MMP-9 expression in plaques (Fig.…”
Section: Discussionsupporting
confidence: 50%
“…Atherosclerosis development is accelerated by salusin-β via increased acyl-coenzyme A:cholesterol acyltransferase-1 expression in human monocyte-derived macrophages, whereas salusin-α may have the opposite effect: serum salusin-α levels are inversely correlated with the maximum intima-media thickness in patients with coronary artery disease [15,16]. Although there is a link between salusin-α and atherosclerosis [11,16,17], it is unclear whether salusin-α plays a role in the proliferation and migration of SMCs, another important cellular event in atherosclerotic lesion formation, even though some reports have shown that salusin-β promotes SMC migration and proliferation and vascular inflammation and fibrosis [18][19][20]. In this study, we attempted to examine the effects of salusin-α on rabbit atherosclerosis, with emphasis on the role of the peptide in SMCs and the underlying mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…As a reactive electrophile, CA could affect Nrf2-independent pathways by directly reacting with other cellular targets. CA may be inhibiting cell proliferation by targeting key pathways such as NF-kB [41], m-TOR [23], or the mitogen-activated protein kinase pathway [42], [43] whose inhibition has been shown to prevent neointimal hyperplasia.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, it has been shown that salusin-β might increase the inflammatory factors by increasing the I-κBa/NF-κB signal pathway activation [21]. Salusin-β weakened the neointima formation stemming from the injury, ROS production, and NOX2 and MMP-9 expression and the p65 translocation of the NF-κB in knock-out rats [42]. In another study, it was reported that salusin-α did not have any effects on IL-1β; however, salusin-β stimulated the expression of IL-1β [43,44].…”
Section: Discussionmentioning
confidence: 93%
“…Our results showed that the caspase-3 expression, which increased in the ethanol-induced ulcer group, decreased after the treatment with salusins. Sun et al [42] conducted a study and reported that salusin-β level increased in relation with the vascular tissue damage. Meanwhile, the protective properties of salusin-α and salusin-β have been reported in myocardial ischemia reperfusion damage [19] and in kidney ischemia reperfusion damage [51].…”
Section: Discussionmentioning
confidence: 99%